Analysis of the Application of PSAK No. 16 in the Accounting Treatment of Fixed Assets in Companies in Indonesia: Literature Study - Atikah Zuhra Sitorus; Marcella Chintya Manao; Salshabilla Nayma; Rizka Dina Aditya; Khofifah; Nur Aliah (Journal of Indonesian Management, 2024)
This study aims to analyze the application of Statement of Financial Accounting Standards (PSAK) No. 16 in the accounting treatment of fixed assets in companies in Indonesia. Fixed assets, which are defined as tangible assets with a useful life of more than one period, play an important role in supporting the company's operational activities. Through a qualitative approach and literature review method, this study collected secondary data from various sources to understand how companies apply this standard. The results show that compliance with PSAK No. 16 improves the transparency of financial statements and supports appropriate managerial decision-making. The implementation of this standard also contributes to the relevance and reliability of financial statements, and assists companies in effectively achieving their operational objectives.